2022
DOI: 10.1155/2022/2320374
|View full text |Cite
|
Sign up to set email alerts
|

Overview: Application of Resin Waterproof Adhesive Materials in Bridge Deck Pavement in China

Abstract: To further promote the research and application of resin type waterproof adhesive layer materials, the types, relevant specifications, and research trends of resin type waterproof adhesive layer in China are comprehensively investigated. The performance evaluation indicators, performance requirement, and requirements in different specifications are systematically analyzed, and the key performance evaluation indicators are recommended. The basic properties of common resin type waterproof adhesive layer material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…When selecting a reasonable adhesive material, not only the adhesive ability of the material but also the stability of the interfacial bonding performance is equally important. Zhou et al [ 38 ] also demonstrated that the resin-type waterproof adhesive layer materials have good impermeability, bonding performance, temperature stability, and construction damage resistance in bridge deck pavement.…”
Section: Resultsmentioning
confidence: 99%
“…When selecting a reasonable adhesive material, not only the adhesive ability of the material but also the stability of the interfacial bonding performance is equally important. Zhou et al [ 38 ] also demonstrated that the resin-type waterproof adhesive layer materials have good impermeability, bonding performance, temperature stability, and construction damage resistance in bridge deck pavement.…”
Section: Resultsmentioning
confidence: 99%
“…У 1960-х роках внаслідок накопичення знань, а також роботи мостового покриву в агресивних середовищах, здебільшого від дії солей, з'явилася концепція водонепроникної системи, з'являються методики дослідження гідроізоляції. В 1976 році в США в Національній програмі спільних досліджень автомобільних доріг (NCHRP) запропоновано випробування ефективності гідроізоляційного матеріалу (Zhou, Zhang, Li, Gao, Chen, & Wang, 2022). А вже 1995 році було узагальнено і вдосконалено старі методи випробування матеріалів для гідроізоляції та висунуто методи випробування та показники оцінки, такі як самостійкість, стійкість до статичного навантаження та просочування води (Manning, 1995).…”
Section: застосування гідроізоляційних систем на основі метилметакрил...unclassified
“…Brücken mit Fahrbаhnplatten aus Beton. Zhou Lu, Zhang Dan, Li Xiaogang, Gao Zhiwei, Chen Qian & Wang Chaohui (2022)…”
Section: Application Of Waterproofing Systems Based On Methyl Methacr...unclassified
“…According to the specifications, the basic properties of asphalt-based waterproof bonding materials mainly include pull-out strength, heat resistance, low temperature flexibility, water permeability resistance, and other properties. When applied to the surface of bridge concrete or steel plate, the amount of waterproof materials should be 0.7-1.0 kg/m 3 [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. We have carried out investigation and statistics on the above properties of the waterproof bonding layer, as shown in Figure 6.…”
Section: Basic Properties Of Asphalt-based Waterproof Bonding Layer M...mentioning
confidence: 99%
“…The SBR-modified emulsified asphalt bonding property statistics [13,22,40,58,59] can be seen in Figure 12. The FYT bonding property statistics [13,24,25,34,[60][61][62] can be seen in Figure 13. The AWP and AMP waterproofing adhesive material bonding property statistics [25,27,29,30,62,63] see Figure 14.…”
Section: Water Emulsion Type Asphalt Waterproof Bonding Layer Materia...mentioning
confidence: 99%